2005
DOI: 10.1074/jbc.m506116200
|View full text |Cite
|
Sign up to set email alerts
|

Saitohin, Which Is Nested in the tau Locus and Confers Allele-specific Susceptibility to Several Neurodegenerative Diseases, Interacts with Peroxiredoxin 6

Abstract: Saitohin is a gene unique to humans and their closest relatives, the function of which is not yet known. Saitohin contains a single polymorphism (Q7R), and its Q and R alleles belong to the H1 and H2 tau haplotype, respectively. The Saitohin Q allele confers susceptibility to several neurodegenerative diseases. To get a handle on Saitohin function, we used it as a bait in a yeast two-hybrid screen. By this assay and subsequent co-immunoprecipitation and glutathione S-transferase pull-down assays, we discovered… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
16
0

Year Published

2007
2007
2015
2015

Publication Types

Select...
8
1
1

Relationship

2
8

Authors

Journals

citations
Cited by 29 publications
(18 citation statements)
references
References 35 publications
(41 reference statements)
2
16
0
Order By: Relevance
“…Several previous studies have demonstrated that Prx6 has unique binding partners such as surfactant protein A and saitohin. 28,29 Interestingly, only Prx6 uses glutathione as a physiological reductant, while other Prxs use thioredoxin. 16 Then, how does Prx6 regulate TRAIL-mediated cell death through DED caspases?…”
Section: Discussionmentioning
confidence: 99%
“…Several previous studies have demonstrated that Prx6 has unique binding partners such as surfactant protein A and saitohin. 28,29 Interestingly, only Prx6 uses glutathione as a physiological reductant, while other Prxs use thioredoxin. 16 Then, how does Prx6 regulate TRAIL-mediated cell death through DED caspases?…”
Section: Discussionmentioning
confidence: 99%
“…High expression of Prdx6 has been noted in degenerative afflictions of the central nervous system, including Alzheimer's (77), Parkinson's (79), Pick's (42), and CrutzfeldJakob diseases (43), schizophrenia (57), and an experimental mouse model of amyotrophic lateral sclerosis (91). As a potential mechanism for some of these associations, binding of Prdx6 to the protein saitohin may be linked to tau splicing and subsequent neurodegeneration (26). Elevated Prdx6 also occurs in various neoplastic diseases, including malignant mesothelioma (40), bronchogenic squamous cell carcinoma (50), and cancer of the gingivo-buccal area (87), bladder (80), and breast (5).…”
Section: Prdx6 In the Pathobiology Of Diseasementioning
confidence: 99%
“…It is highly expressed in the placenta, muscle, fetal brain and adult brain. In numerous association studies [30][31][32], it has been shown to interact with tau, but also with peroxiredoxin 6 [33], which has antioxidant and phospholipase activity, and with the Abelson kinase [34]. Interestingly, Abelson is widely expressed but is notably highly expressed in hyaline cartilage [35], which could give us a link to the dysmorphic features involving notably the nose in affected patients.…”
Section: Discussionmentioning
confidence: 93%